Extending letrozole treatment to 10 years may prevent recurrent breast cancer. Issue 5 (May 2017) - Thompson, Richard; O'Mara, Heather; Neff, Laurel; Arnold, Mike
Abstract : N/A: Goss PE, Ingle JN, Pritchard KI, et al. Extending aromatase‐inhibitor adjuvant therapy to 10 years. N Engl J Med . 2016; 375(3):209–219.